Screening and validation of prognostic indicator genes in the progression of HBV related hepatocellular carcinoma - Jinglin Wang; Senzhe Xia; Yuyan Chen; Xueqian Qin; Shujun Liu; Haozhen Ren (Biomedical Technology, 2023)
Hepatocellular carcinoma (HCC) is a rapidly progressing cancer and the main reason for cancer-related deaths. There are numerous risk factors for HCC, of which hepatitis B virus (HBV) infection is recognized as a high risk. HBV infection is accompanied by gene integration, and the liver has undergone the process of continuous and repeated damage and repair. However, predictive factors of HBV-related HCC are still limited, and the prognostic regulatory genes have not been fully elucidated. This study aims to use bioinformatics analysis to search potential prognostic genes of HBV-related HCC. Based on the full utilization of the GEO database, we screened out prognostic-related genes by performing systematic Kaplan-Meier survival analysis. The differences of the transcriptional information and protein expression were verified in the TCGA and HPA databases respectively, and the clinical characteristics of the screened genes were described by the boxplot. Five prognostic-related genes we screened, including CDK1, MAD2L1, SPP1, TYMS, and CCNA2, are strongly linked with poor prognosis in HBV-related HCC. The five prognostic-related genes have realistic clinical significance and potential as prognostic markers, and may provide new directions for basic research and clinical diagnosis.